MATHEMATICS CONNECTION ABILITY FOR JUNIOR HIGH SCHOOL STUDENTS BASED ON LEARNING INDEPENDENCE LEVEL - Samudro, Galleh Dwi; Shodikin, Ali (Jurnal Pendidikan Matematika (JUPITEK), 2022)
Mathematical connection ability is one of the basic mathematics skills that must be possessed by junior high school students. It turns out that so far, the student's learning outcomes in terms of mathematics have not been encouraging. This study aims to describe the mathematical connection skills of junior high school students in solving a problem in terms of learning independence. This research is a qualitative descriptive study on eighth-grade students in a junior high school in Lamongan district, East Java. Data was collectied using test questions, interviews, and questionnaires. This study obtained the following results: 1) one subject (S2) who has high mathematical connection ability with low learning independence, 2) one subject (S1) who has moderate mathematical connection ability with moderately high learning independence, and 3) two subjects (S3 & S4) who have low mathematical connection skills with low learning independence. The internal causes of the lack of mathematical connection skills and student learning independence are the lack of practice questions, the lack of motivational stimulus to encourage students to study independently. While external factors are the level of test questions that are tested too difficult and the lack of supporting learning information sources